Effectiveness of Judicial Conduct Supervision in Regional Institutional Practice - Miftahul Huda; Yvonne Wangdra; Diki Zukriadi; Lenny Husna; Padrisan Jamba (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the effectiveness of judicial conduct supervision at the regional level within the framework of Indonesia’s judicial oversight system. The research focuses on how supervisory functions are implemented in practice, including the identification of institutional constraints that affect their performance. The research method used in this study is a sociological legal (socio-legal) approach with a descriptive qualitative design. Primary data were obtained through field observations and in-depth interviews with officials at the regional liaison office, while secondary data were derived from statutory regulations, legal literature, and relevant scholarly works. The novelty of this research lies in its focus on the empirical implementation of judicial conduct supervision at the regional level, particularly in highlighting the gap between the normative framework and actual practice. Unlike previous studies that emphasize institutional authority at the central level, this study provides a contextual analysis of operational challenges, including limited human resources, budget constraints, bureaucratic complexity, and the absence of adaptive regulatory mechanisms for supervising online court proceedings. Based on the research, it is concluded that although the supervisory function has a clear legal foundation and institutional mandate, its implementation has not yet achieved optimal effectiveness. Structural limitations and centralized authority significantly affect the responsiveness and flexibility of supervision at the regional level. Therefore, strengthening institutional capacity and developing more adaptive regulatory frameworks are necessary to enhance the effectiveness of judicial conduct supervision.